Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
BACKGROUND: Early prognostic assessment after traumatic brain injury (TBI) is challenging because the neurological examination at bedside shows the initial severity of the injury but does not fully describe the evolution of secondary brain injury. METHODS: This single-center retrospective study included 356 eligible patients with TBI. Patients admitted between January 2024 and December 2024 formed the training cohort, and those admitted between January 2025 and January 2026 formed the temporal validation cohort. Demographic and clinical data were collected, including age, etiology, presenting symptoms, admission Glasgow Coma Scale (GCS) score, pupil reactivity, Rotterdam computed tomography (CT) score, transcranial Doppler (TCD) findings, mean edema coefficient (EC), mean noninvasive intracranial pressure (nICP) during the first monitoring session, surgery during hospitalization, and 3-month Glasgow Outcome Scale (GOS) score. Logistic regression analyses were performed in the training cohort and assessed in the temporal validation cohort. RESULTS: The final analysis included 181 patients in the training cohort and 175 in the temporal validation cohort. Unfavorable 3-month outcome occurred in 95 patients (52.5%) and 103 patients (58.9%), respectively. Lower admission GCS, abnormal TCD findings, and a higher mean EC were independently associated with an unfavorable outcome. The area under the curve was 0.857 in the training cohort and 0.846 in the temporal validation cohort; the corresponding Brier scores were 0.154 and 0.175. CONCLUSIONS: Admission GCS, TCD abnormalities, and greater early edema burden were associated with a 3-month unfavorable outcome after TBI. Combining routine admission assessment with early bedside noninvasive monitoring may aid early risk stratification.